Bank performance and real sector productivity in East Africa - Odongo Kodongo (Kenya Bankers Association (KBA), 2024)
This paper sought to establish the linkages between bank performance and real sector productivity. We use data for five East African countries (Ethiopia, Kenya, Rwanda, Tanzania, and Uganda) for the period 2014-2022. We initially deploy the traditional panel fixed effects regression and subsequently the instrument variable fixed effects estimation for robustness checks. Our results show a robust negative nexus between banking sector performance and real sector productivity. Second, we find that noninterest charges is the major channel of transmission of adverse effects from the banking sector to real sectors such as manufacturing, while the interest channel tends to transmit positive effects especially to the services sector. Based on these findings, we make several policy recommendations.
Keywords: 330; Real sector productivity; sectoral value-added; bank profitability; cost efficiency; East Africa